Correlates of obsessive-compulsive and related disorders symptom severity during the COVID-19 pandemic. (November 2021) - Fontenelle, Leonardo F.; Albertella, Lucy; Brierley, Mary-Ellen; Thompson, Emma M.; Destrée, Louise; Chamberlain, Sam R.; Yücel, Murat
Abstract: We investigated changes in the severity of obsessive-compulsive and related disorders (OCRDs) symptoms as a result of the COVID-19 pandemic. An Amazon Mechanical Turk sample of 829 individuals was evaluated with a series of instruments assessing the severity of the OCRDs before and during the pandemic. Additional questionnaires about sociodemographic factors, personal and family histories of OCRD, COVID-19 related events, compulsivity and impulsivity traits, schizotypal symptoms, and the severity of depression, anxiety and stress levels, were also used. Participants reported that OCD, hoarding disorder (HD) and skin picking disorder (SPD) symptoms significantly worsened during the pandemic along with increased disability, more affective symptoms and reduced quality of life. Female gender, a higher number of COVID-19 related stressful events, and higher pre-COVID-19 fear of harm and symmetry symptoms predicted more severe OCD symptoms during the pandemic, whereas lack of a HD diagnosis by a mental health professional and more severe schizotypal symptoms predicted worsened hoarding symptoms. Greater compulsivity traits were associated with more severe COVID-19 pandemic obsessive-compulsive and hoarding symptoms. These data indicate that the immense distress resulting from the COVID-19 included significant deterioration of OCRDs' symptoms, particularly of OCD, HD and SPD. It was also possible to identify a pre-pandemic profile of people most at risk of pandemic-related deterioration in OCRDs' symptoms, which may prove valuable for preventative initiatives in relation to the likely future waves of COVID-19 or of other communicable diseases. Future studies should follow up these findings longitudinally. Highlights: OCD, hoarding disorder and skin picking disorder significantly worsened during the pandemic. Female gender, COVID-19 stressful events, fear of harm and symmetry predicted more severe pandemic OCD. Lack of a diagnosis and schizotypal traits predicted more severe pandemic hoarding. Greater compulsivity traits were associated with more severe pandemic OCD and hoarding.